Complex Macrophase‐Separated Nanostructure Induced by Microphase Separation in Binary Blends of Lamellar Diblock Copolymer Thin Films. Issue 18 (26th August 2014) - Zhang, Jianqi; Posselt, Dorthe; Smilgies, Detlef‐M.; Perlich, Jan; Kyriakos, Konstantinos; Jaksch, Sebastian; Papadakis, Christine M.
<x xml:space="preserve">Abstract</x> The nanostructures of thin films spin‐coated from binary blends of compositionally symmetric polystyrene‐b‐polybutadiene (PS‐b‐PB) diblock copolymer having different molar masses are investigated by means of atomic force microscopy (AFM) and grazing‐incidence small‐angle X‐ray scattering (GISAXS) after spin‐coating and after subsequent solvent vapor annealing (SVA). In thin films of the pure diblock copolymers having high or low molar mass, the lamellae are perpendicular or parallel to the substrate, respectively. The as‐prepared binary blend thin films feature mainly perpendicular lamellae in a one‐phase state, indicating that the higher molar mass diblock copolymer dominates the lamellar orientation. The lamellar thickness decreases linearly with increasing volume fraction of the low molar mass diblock copolymer. After SVA, well‐defined macrophase‐separated nanostructures appear, which feature parallel lamellae near the film surface and perpendicular ones in the bulk. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>